Inculcating Siri’ Na Pacce Value in Primary School Learning - Azis, Abdul; Saleh, Sitti Fithriani; Suriani, Ade Irma (Mimbar Sekolah Dasar, 2020)
Siri' na pacce is the local wisdom of the Bugis-Makassar tribe. Siri' embodies the unification of the attitude of shame and self-esteem, while pacce embodies an attitude of compassion and solidarity. This research aims at describing teachers’ perceptions about the inculcation of siri’ na pacce value in primary school learning and teaching practices. This research involved 102 primary school teachers in Makassar, Indonesia. The research instruments were questionnaires, interview guidelines, and recorded observations of learning. The majority of participants believed the value of siri' na pacce is still relevant to current conditions and realized their essential role in conveying it to students. Most participants thought that the value of siri' na pacce needs to be integrated into learning, although there were participants who thought it is difficult to do. More than 50% of participants stated that they always or often conveyed siri’ na pacce value to students both inside and outside the classroom. However, less than 50% of participants regularly or frequently consider how to integrate these values into learning. The activities of integrating siri' na pacce value conducted by the teacher in learning were not well planned yet.